Lysing Agents for Characteristic Polluting Microorganisms in Jet Fuels - Yun Xiong; Xinfeng Sun; Peng Zhu; Mingming Niu; Peng Su (International Journal Bioautomation, 2019)
The adenosine triphosphate (ATP) bioluminescence assay is a feasible way to quantify the characteristic polluting microorganisms of the jet fuels. The effect of this method hinges on the release of ATP through the effective lysis of microorganisms. To achieve a good microbial lysis effect, this paper explores the fungi lysis effects of two quaternary ammonium salts, benzyldodecyldimethylammonium bromide (BAB) and benzalkonium chloride (BAC), and discusses the impacts of the two cationic surfactants on luciferase activity. The results show that BAB was more effective than BAC in the lysis of the characteristic polluting fungi, putting the optimal BAB concentration at 0.05%; traditional lysing agents like cetyl trimethyl ammonium bromide (CTAB) and trichloroacetic acid (TCA) had poor effects on fungi lysis; 0.025% Hibitine and 0.05% BAB exerted a synergistic effect on the lysis of characteristic polluting fungi, and were identified as the preliminary components of the lysing agent for the characteristic polluting microorganisms of jet fuels; the optimized luciferase-luciferin reaction system effectively mitigated the suppression effect of the lysis agent on enzymatic activity, and the ATP standard curves with or without lysing agent had no significant difference (p = 0.9768 > 0.05). The optimized luciferase-luciferin reaction system, coupled with the mixture of BAB and Hibitine, outshines the traditional plate culture method and HY-LiTE JET A1 Fuel Test in detection efficiency and cost.